A Decade of Transition : Achievements and Challenges - Nsouli, Saleh (International Monetary Fund, 2001)
This volume reviews the experience of 25 non-Asian transition economies 10 years into their transformation to market economies. The volume is based on an IMF conference held in February 1999 in Washington, D.C., to take stock of the achievements and the challenges of transition in the context of three questions: How far has transition progressed ineach country? What factors explain the differences in the progress made? And what remains to be done?